The effect of occupational health and safety on the performance of employee of Tire Industry Indonesia - Indra Setiawan; Niko Farid Aldrianto; Djauhar Arifin; Wahyu Inggar Fipiana; Vivi Lusia (Journal Industrial Servicess, 2022)
Tire Industry Indonesia Bekasi Plant is a manufacturing company that produces vehicle tires, tubes, and flaps. The production process in the Indonesian Tire Industry uses a lot of dangerous equipment and machines production process so that it can affect the safety and health of employees. During 2020, work accidents increased which caused employee performance to decline and resulted in decreased productivity. This study aims to analyze employee performance which is influenced by Occupational Safety and Occupational Health in the Indonesian Tire Industry. The results of the questionnaire from the respondents as many as 200 people in the production section were analyzed by linear regression. This research uses the help of Ms. Excel and SPSS v.17 software. Based on the results of the study, it is known that partially occupational safety and health have no significant effect on employee performance. In addition, it is also known that simultaneously there is a significant influence between the variables of Occupational Safety and Health on Employee Performance.